Considerations for the Surgical Management of Thoracic Cancers During the COVID-19 Pandemic: Rational Strategies for Thoracic Surgeons - Zhang, Jiahao; Han, Yichao; Zhang, Yajie; Dong, Dong; Cao, Yuqin; Chen, Xiang; Li, Hecheng (Frontiers in Surgery, 2022)
Objective The novel Coronavirus Disease 2019 (COVID-19) has resulted in a global health crisis since first case was identified in December 2019. As the pandemic continues to strain global public health systems, elective surgeries for thoracic cancer, such as early-stage lung cancer and esophageal cancer (EC), have been postponed due to a shortage of medical resources and the risk of nosocomial transmission. This review is aimed to discuss the influence of COVID-19 on thoracic surgical practice, prevention of nosocomial transmission during the pandemic, and propose modifications to the standard practices in the surgical management of different thoracic cancer. Methods A literature search of PubMed, Medline, and Google Scholar was performed for articles focusing on COVID-19, early-stage lung cancer, and EC prior to 1 July 2021. The evidence from articles was combined with our data and experience. Results We review the challenges in the management of different thoracic cancer from the perspectives of thoracic surgeons and propose rational strategies for the diagnosis and treatment of early-stage lung cancer and EC during the COVID-19 pandemic. Conclusions During the COVID-19 pandemic, the optimization of hospital systems and medical resources is to fight against COVID-19. Indolent early lung cancers, such as pure ground-glass nodules/opacities (GGOs), can be postponed with a lower risk of progression, while selective surgeries of more biologically aggressive tumors should be prioritized. As for EC, we recommend immediate or prioritized surgeries for patients with stage Ib or more advanced stage and patients after neoadjuvant therapy. Routine COVID-19 screening should be performed preoperatively before thoracic surgeries. Prevention of nosocomial transmission by providing appropriate personal protective equipment (PPE), such as N-95 respirator masks with eye protection to healthcare workers, is necessary.